IL-37 mediates the anti-tumor activity in non-small cell lung cancer through IL-6/STAT3 pathway - Deng, Yan-Ming; Zhang, Hua; Liang, Jian-Miao; Xian, Hai-Bing; Chen, Ze-Cheng; Tang, Yi-Cong; Yang, Shuang; Feng, Wei-Neng (Journal of Applied Biomedicine, 2018)
The occurrence and development of lung cancer is closely related to inflammation. Thus, we conducted the present study to investigate the effects of IL-37 (Interleukin 37), a newly identified anti-inflammatory factor, on non-small cell lung cancer (NSCLC), which accounts for about 85% of all lung cancers. To address the function of IL-37 in NSCLC, we first evaluated IL-37 expression in the human NSCLC tissues; then the IL-37 function was assessed in vitro and in vivo in a xenografted lung tumor model. IL-37 was barely expressed in the NSCLC tissue but highly expressed in the adjacent normal tissue. This expression profile was validated by ELISA (Enzyme-linked immunoassay), western blot and immunohistochemical staining. Recombinant IL-37 could suppress cell migration, invasion and proliferation and promote cell apoptosis in NSCLC cell line A549 and SK-MES-1. IL-37 inhibited the IL-6/STAT3 pathway and also the downstream targets Bcl-2, NEDD9 and Cyclin D1. Overexpressing IL-6 or constitutive active STAT3 eliminated the anti-tumor effects of IL-37. Furthermore, IL-37 expression in vivo could inhibit the cancer development. Our results showed that IL-37 plays an inhibitory role in lung cancer development, possibly through IL-6/STAT3 pathway.
Keywords: STAT3 Transcription Factor; nádorová transformace buněk; Cell Transformation, Neoplastic; Humans; receptory interleukinu-6; interleukin-1; mediátory zánětu; lidé; Inflammation Mediators; transkripční faktor STAT3; Interleukin-1; Carcinoma, Non-Small-Cell Lung; signální transdukce; nemalobuněčný karcinom plic; Receptors, Interleukin-6; Signal Transduction